Digital electronics. sequential and arithmetic logic circuits - Ndjountche, Tertulien (Electronics engineering series (London, England), 2016)
The book presents the principles of combinational and sequential logic and the underlying techniques for the analysis and design of digital circuits. The approach is gradual and relatively independent of each other chapters. To facilitate the assimilation and practical implementation of various concepts, the book is complemented by a selection of practical exercises corrected. It deals with the analysis and design digital circuits, logic gates to machinery (PLCs) with a finite number of states, and contains 14 chapters divided into 4 volumes.